2016
DOI: 10.1161/atvbaha.116.307639
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting GPIbα Shedding Preserves Post-Transfusion Recovery and Hemostatic Function of Platelets After Prolonged Storage

Abstract: Objectives The platelet storage lesion accelerates platelet clearance after transfusion, but the underlying molecular mechanism remains elusive. Although inhibiting sheddase activity hampers clearance of platelets with storage lesion, the target platelet protein responsible for ectodomain shedding-induced clearance is not definitively identified. Monoclonal antibody 5G6 was developed recently to bind specifically human platelet receptor GPIbα and inhibit its shedding but not shedding of other receptors. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 41 publications
1
53
0
Order By: Relevance
“…If GPIbα shedding is secondary to a damaging event, then shedding inhibitors will not help but in the case that shedding sparks downstream lesions, inhibitors may be able to mitigate damage. For age‐related storage lesion of liquid PLTs, specific inhibition of GPIbα shedding rescued the rapid clearance of aged PLTs to some extent . Future research can always exploit the GPIbα‐dim subpopulation as a biomarker for the extent of damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If GPIbα shedding is secondary to a damaging event, then shedding inhibitors will not help but in the case that shedding sparks downstream lesions, inhibitors may be able to mitigate damage. For age‐related storage lesion of liquid PLTs, specific inhibition of GPIbα shedding rescued the rapid clearance of aged PLTs to some extent . Future research can always exploit the GPIbα‐dim subpopulation as a biomarker for the extent of damage.…”
Section: Discussionmentioning
confidence: 99%
“…For age-related storage lesion of liquid PLTs, specific inhibition of GPIbα shedding rescued the rapid clearance of aged PLTs to some extent. 34 Future research can always exploit the GPIbα-dim subpopulation as a biomarker for the extent of damage. The impact of directed modifications in the cryoprocess can be easily monitored using this particular marker in flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…Forskolin also significantly inhibited ΔΨ m depolariza- vation of p38 MAPK and p38 MAPK-mediated cytosolic phospholipase A2, resulting in release of arachidonic acid from membrane phospholipids, which transfers 14-3-3 to the cytoplasmic domain of GPIbα (48,49). In the meantime, p38 MAPK activates ADAM17, leading to GPIbα ectodomain shedding (47), which enhances GPIbα clustering and association of 14-3-3 with the cytoplasmic domain of GPIbα (50). 14-3-3 competes with BCL-XL to bind BAD, thus increasing 14-3-3-GP1ba interaction (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…However, although the enzymes were inhibited, the alleviation for storage lesion was not significant. It is noteworthy that, despite the mechanism remaining unclear, inhibition of p38 MAPK (46) or p38 MAPK-mediated GPIbα shedding (46,47) significantly improves the quality and posttransfusion survival and function of stored platelets. We and others previously reported that GPIbα-dependent signaling could induce platelet apoptosis and that association of 14-3-3 with the cytoplasmic domain of GPIbα is essential for apoptotic signaling (7, 48, 49).…”
Section: Methodsmentioning
confidence: 99%
“…Shedding of GPIbα in platelets during storage at RT is well documented. Inhibition of GPIbα shedding by inhibitors of ADAM17 activity or an anti-GPIbα antibody improves the post-transfusion recovery of RT-stored platelets 3840 . Little GPIbα shedding was observed after refrigeration of Adam17 ΔZn/ΔZn murine platelets that express only an inactive ADAM17, but refrigerated Adam17 ΔZn/ΔZn platelets were cleared as rapidly as the WT control 5 .…”
Section: Discussionmentioning
confidence: 99%